Skeletal Metastasis From Carcinoma of the Gall Bladder: Need for Bone Scintigraphy Justified? - Aswani, Yashant (Pol J Radiol, 2016)
BACKGROUND: Carcinoma of the gall bladder has a guarded prognosis with predominant sites of involvement being liver and regional nodes. Osseous metastasis in carcinoma of the gall bladder is rare and hence bone scintigraphy does not form a part of the routine work-up for such patients. CASE REPORTS: We describe two patients with carcinoma of the gall bladder with osteolytic metastasis (stage 4). Conservative treatment was planned but both of them succumbed to the illness. CONCLUSIONS: We thus highlight the importance of performing a bone scan or PET CT in cases of carcinoma of the gall bladder. Besides, our cases challenge Paget’s seed – soil theory for sites of metastasis.